College Sports Competitive Balance "Beliefs" and the Rule of Reason: Applied Theory and a Literature Review. (March 2017) - Fort, Rodney
In college sports antitrust cases where the rule of reason is applied, courts weigh the anticompetitive effects of, say, the amateur requirement against a presumed welfare offset, say, enhanced competitive balance. This article examines these "belief" underpinnings. Theoretically, whether fans prefer more balance is a hypothesis about preferences. As such, it needs to be examined empirically in every case. The limited empirical work on attendance and TV viewing supports the hypothesis for the top-level teams in FBS football, but not for any other college football, and there is no work on basketball. Applied theory also suggests that neither the amateur requirement nor mobility restrictions enhance balance as claimed. The empirical work is even more limited on this question and supports the theory for football, but not for basketball. However, the only evidence on basketball is that the amateur requirement makes balance worse. Finally, applied theory suggests that revenue sharing can improve balance, but only under specific circumstances. There is no additional empirical work on this question, but indirectly past work finds no impacts of revenue sharing on competitive balance. Ultimately, then, the answer to the rule of reason question may only be settled empirically, and there is only limited help in the extant literature on college sports. Understanding these issues leads to a clear prescription for courts to follow.